(untitled) (Al Dzahab, 2025)
Purpose: This study aims to empirically examine the influence of Accounting Information Systems (AIS) on Financial Report Accuracy, Information Presentation Speed, and Tax Compliance among Micro, Small, and Medium Enterprises (MSMEs) in Sumbawa Regency. Design/Methodology/Approach: The research employs a quantitative approach with an explanatory design to explain the causal relationships between variables. The sample consists of 310 MSME actors in Sumbawa Regency selected using proportional stratified random sampling. Data were collected through questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Findings: The results show that Accounting Information Systems have a positive and significant effect on Financial Report Accuracy, Information Presentation Speed, and Tax Compliance. Collectively, the research model demonstrates moderate to strong predictive power. Research Implications: To improve the quality of financial reporting and fundamentally address tax compliance issues, interventions should focus on facilitating and accelerating the adoption of AIS. Investments in training, mentoring, and providing access to affordable AIS are essential strategies for building a strong foundation of financial governance, which in turn will enhance sustainable compliance and optimize the potential of regional tax revenues.